Pens for Hire - Buerger, Geoff E. (Canadian Perspectives on Academic Integrity, 2021)
This is part one of a three part invited article series examining the historical evolution of the “ghost writing” industry, a term that is now widely referred to as “contract cheating.” This article describes the commercial trade in academic work starting in the 1930s through the term paper mills’ heyday of the mid-1970s. The 1960 investigative reporting of Alex Benson of the New York World-Telegram and The Sun, receives close attention, as does the field of competing firms active at the University of Wisconsin at Madison in 1972. The article concludes with a series of questions to help provoke reflection. These questions can be used as discussion topics in courses with students or within professional development opportunities for educators and practitioners.